1995
DOI: 10.1007/bf02648212
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for phonological processing deficits in less-skilled readers

Abstract: Although weaknesses in metaphonological skills are well-documented in poor readers, prior studies have yielded inconsistent findings as to whether less-skilled readers also have deficits in the more primary phonological processes entailed in verbal working memory and speech production tasks. The present study was designed to examine this issue by comparing less-skilled third-graders readers (n=30) with younger children at the same reading level (n=30) and with more-skilled agemates (n=30) on a variety of tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 52 publications
3
34
0
5
Order By: Relevance
“…In a follow-up study, Snowling and colleagues (Snowling, Goulandris, Bowlby, & Howell, 1986) found that dyslexic children performed worse in repetition of low-frequency real words and nonwords when compared to age-matched and reading-matched children. Subsequent studies have further confirmed these findings (Catts, 1986;Kamhi, Catts, Mauer, Apel, & Gentry, 1988;Stone & Brady, 1995).…”
Section: Phonological Memorysupporting
confidence: 70%
See 1 more Smart Citation
“…In a follow-up study, Snowling and colleagues (Snowling, Goulandris, Bowlby, & Howell, 1986) found that dyslexic children performed worse in repetition of low-frequency real words and nonwords when compared to age-matched and reading-matched children. Subsequent studies have further confirmed these findings (Catts, 1986;Kamhi, Catts, Mauer, Apel, & Gentry, 1988;Stone & Brady, 1995).…”
Section: Phonological Memorysupporting
confidence: 70%
“…Phonological memory has been assessed through memory span tasks involving strings of verbal items, such as digits, letters, and words. Children with RD perform poorly on these tasks when compared to good readers (Cohen & Netley, 1981;Mann, Liberman, & Shankweiler, 1980;Rapala & Brady, 1990;Shankweiler, Liberman, Mark, Fowler, & Fischer, 1979;Stone & Brady, 1995).…”
Section: Phonological Memorymentioning
confidence: 91%
“…Al igual que algunos estudios previos (Baqués & Sáiz, 1999;Pickering, 2006;Stone & Brady, 1995), la presente investigación muestra que los niños con trastornos en el aprendizaje de la lectura (TAL y TAL/TAM) presentan un déficit en el componente del Bucle Fonológico del modelo de memoria operativa de Baddley y Hitch (1974), aunque el grupo con TAL sólo evidenció un déficit significativo en Retención Directa de Dígitos.…”
Section: Discussionunclassified
“…Este hallazgo no es consistente con estudios previos que muestran que la repetición de pseudopalabras es significativamente inferior en niños con TAL debido a las dificultades relacionadas con la decodificación lectora cuando se utiliza la ruta fonológica para una adecuada conversión grafema-fonema. En general, se ha considerado que este tipo de pruebas contribuye en la evaluación de las representaciones fonológicas requeridas para el aprendizaje de la lectura (De Jong & Olson, 2004;Pickering, 2006;Stone & Brady, 1995).…”
Section: Discussionunclassified
“…Με βάση μελέτες που διαπίστωσαν ότι η φωνολογική βραχύχρονη μνήμη προβλέπει την αναγνωστική επίδοση (Stone & Brady, 1995• Aro, et al, 2004• Seigneuric, 2005) υποθέτουμε ότι η φωνολογική βραχύχρονη μνήμη στην προσχολική ηλικία θα προβλέψει την αναγνωστική επίδοση στις μετέπειτα βαθμίδες.…”
Section: η υπόθεσηunclassified